Parameters and genetic trends for reproductive characteristics of a closed Angus herd - Falleiro, Vanius B.; Carneiro, Paulo L. S.; Carrilo, Jose A.; Rezende, Marcos P. G.; Cervini, Marcelo; Malhado, Carlos H. M. (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Closed breeding populations are usefull to conduct basic and applied research. The Wye Angus herd is one of them. It was founded using only a few animals. The pedigree of the descendants of the original herd can be completely described by historical records resulting from strong selection. Wye Angus genetics has influenced that of Aberdeen Angus, Red Angus, and Brangus cattle worldwide. Objective: To evaluate parameters and genetic trends associated with the reproduction traits of the Wye Angus herd between the years 1937 and 2012. Methods: We used pedigree information of 11,692 individuals. The reproductive traits assessed were age at first calving (AFC), calving interval (CI), and scrotal circumference (SC). The covariance components were estimated by Bayesian inference. The genetic trends were obtained by linear regression of the genetic values over birth years of the animals. Results: The heritability estimates for AFC, and CI were negligible, although a small genetic gain was associated with CI. Because the AFC and CI values of the herd are small, past reproductive management has produced favourable results for the heifers. Conclusion: The Wye Angus herd has enough genetic variability for genetic gain through selection on SC.